Preoperative Delirium Nursing Model Initiatives to Determine the Incidence of Postoperative Delirium Among Elderly Orthopaedic Patients. (March 2021) - Wu, Huixin; Kapur, Anshika; Gibson, Barbara; Bubb, Kelsi; Alrawashdeh, Mohammad; Cipkala-Gaffin, Janet
Abstract : Delirium is a common neurocognitive disorder prevalent in hospitalized older adults. The development of delirium is associated with adverse health outcomes, including functional decline and mortality. This study aimed to investigate the incidence and risk factors of postoperative delirium in older adults (≥60 years) who underwent orthopaedic surgery. Elderly orthopaedic patients were recruited from a large urban hospital over 12 months. Patients were preoperatively screened for delirium and followed up at least once daily postoperatively until discharge. Of the 124 patients in the sample, 21 (16.9%) had postoperative delirium. There were no significant differences in any of the baseline characteristics between the delirious and nondelirious patients. Patients using antidepressants were more likely to develop postoperative delirium compared with those not using antidepressants (odds ratio: 2.72, p = .05). Postoperative delirium was common in this sample of older adults who underwent orthopaedic surgery. Aiming prevention strategies toward patients using antidepressants may help reduce the incidence of delirium in this population.